2016
DOI: 10.15560/12.3.1892
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian fauna of Rajaji National Park, India: a review on ecological observations and checklist

Abstract: Rajaji National Park, in the Gangetic Plains biogeographic zone, has a diverse and biogeographically important mammalian assemblage. In the recent past, several studies on the herbivores, large carnivores and mega-herbivores have been carried out, but limited work has been done on the distribution of mammals in the park. This study illustrates the ecological observations and review of the mammals of the Rajaji National Park, based on field surveys, carried out during 2006-2008, using direct and indirect sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The presence of Indian Pangolin has been documented across the Shivalik hills in India (~300-1,000 m) (Joshi 2016;Bhandari et al 2019;Kumar et al 2022). Although this is the first photographic evidence regarding the presence of species in SNP, its presence has been reported in a few studies conducted in the National Park (Bhargav 2009;Chand 2014); however, no further information or evidence was provided.…”
Section: Discussionmentioning
confidence: 97%
“…The presence of Indian Pangolin has been documented across the Shivalik hills in India (~300-1,000 m) (Joshi 2016;Bhandari et al 2019;Kumar et al 2022). Although this is the first photographic evidence regarding the presence of species in SNP, its presence has been reported in a few studies conducted in the National Park (Bhargav 2009;Chand 2014); however, no further information or evidence was provided.…”
Section: Discussionmentioning
confidence: 97%
“…The annual rainfall varies 1,200-1,500 mm. Within a 5-km radius of RTR, there are over 100 settlements, but our study area consists of 13 villages with a total population of 28,449 with 13,170 male and 15,279 female (Uttarakhand Population census 2011), and many of the population rely on adjacent forest resources such as fuelwood, fodder, grass, livestock foraging ground, and locally available non-timber forest products (Badola 1997;Chandola et al 2007) (Joshi 2016). Motichur and Shyampur ranges were chosen based on the recommendations of forest department employees and local key informants, who reported a high prevalence of conflict in these two ranges.…”
Section: Study Areamentioning
confidence: 99%
“…Impact of plastic pollution has been under-reported for terrestrial environments in comparison to marine environments (Malizia & Monmany-Garzia, 2019), especially in rivers, deep forests due to heterogenous distribution of plastics on land (Jambeck et al, 2015;Ng et al, 2018;Malizia & Monmany-Garzia, 2019). Though few recent studies have demonstrated its impacts on a variety of soil organisms (Liu et al, 2017;de Souza Machado et al, 2018a, 2018b including earthworms (Lwanga et al, 2017) and snails (Panebianco et al, 2019) (Johnsingh & Negi, 2003;Joshi, 2016;Paul et al, 2020). This landscape holds three Protected Areas i.e., Rajaji National Park, Corbett National Park and Jhilmil Jheel Conservation Reserve, amidst a mosaic of non-protected forest habitats and dense human habitations signifying its conservation importance.…”
Section: Introductionmentioning
confidence: 99%
“…These study sites are part of north-western Terai-Arc Landscape, an important landscape for conservation of several threatened species such as tiger Panthera tigris, leopard Panthera pardus, northern swamp deer Rucervus duvaucelii duvaucelii and Asian elephant Elephas maximus (Johnsingh & Negi, 2003;Joshi, 2016;Paul et al, 2020). This landscape holds three Protected Areas i.e., Rajaji National Park, Corbett National Park and Jhilmil Jheel Conservation Reserve, amidst a mosaic of non-protected forest habitats and dense human habitations signifying its conservation importance.…”
Section: Introductionmentioning
confidence: 99%